If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2y + 6 = -6 Reorder the terms: 6 + -2y = -6 Solving 6 + -2y = -6 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -2y = -6 + -6 Combine like terms: 6 + -6 = 0 0 + -2y = -6 + -6 -2y = -6 + -6 Combine like terms: -6 + -6 = -12 -2y = -12 Divide each side by '-2'. y = 6 Simplifying y = 6
| 2y+4-2=8 | | y^3-3ay^2+3a^2y-a^3=0 | | m-(-0.7)=1.2 | | -2y+6=6 | | 3.4=0.8+z | | 0.5x+2=0.75x | | 2(5x-25)=10(x-f) | | 15x=-2 | | 58-0.15(58)= | | 35y+0.10=25y+0.25 | | 5xy-12xy= | | 2x^2+6x=176 | | 6y-7=1 | | 4x=400 | | 14x+5=7x+7 | | v=16*9*7 | | 1-12v-4=33 | | 5=x-8 | | 3x+4=4x+6 | | 0.6(2m-10)+0.66=10 | | y=cx+s | | c=cx+s | | 9u^3+15u^2-36u=0 | | c=cx | | 0.5(14-x)=4 | | -4p(3p+4)-11=3(4p+7) | | 0.692m-10=0.6m+10 | | 14t-8=-20 | | -x-4x=8 | | 8x=3y-7 | | 14=-9p-80 | | 9(4x-4)=3(12+2) |